Análisis de la Sostenibilidad de Predios Agrícolas de Maíz y Frejol en el Barrio Rumipamba del Cantón Chillanes Provincia de Bolívar - Cevallos Quinatoa, Katy Elizabeth (2018)
In the province of Bolívar, the cultivation of soft corn is predominant, with this item occupying the first place in importance, with an area that exceeds 13,875 hectares. It is necessary to implement a plan to boost agricultural production socially and economically with good practices, aimed at the socio-ecological sustainability of the community. In the Rumipamba neighborhood of the Chillanes Canton of the Province of Bolívar, corn and bean production systems were evaluated, applying the Evaluation of Natural Resources Management Systems (MESMIS). It was found that 33.33% of the UPAs show a surface between 0.25 and 0.4 ha. Only 16.67% of the UPAs have a surface area greater than 1ha. The maximum surface area observed was 1.63 ha. In the UPAs evaluated in the Rumipamba neighborhood, it was observed that the agricultural subsystem shows a distribution of 50% of corn, and 50% of beans. The livestock subsystem showed a distribution of 2 to 7 bovine units per UPA.The forest subsystem was found from 15 to 50 adult trees per UPA, of the species eucalyptus (Eucalyptus sp) avocado (Persea americana) cypress (Cupressus) Alder (Alnus glutinosa) chilca (Baccharis latifolia) milk (Euphorbia laurifolia) Zapa (Caesalpinia sappan ). The indicators of soil fertility, seeds for planting, management of the cultivation of corn and beans, cultural work, type of planting, harvesting and storage, type of transport to the market. They are sustainable with an index 5 on the MESMIS scale. The control indicators of pests and diseases, dependence on external inputs, knowledge at the time of pre-sowing, access to the market, tend to be sustainable with an index 4. The practice of monoculture reduces the sustainability of the system with an index of 3.